Fast liquefaction of bamboo shoot shell with liquid-phase microplasma assisted technology. (October 2016) - Zhou, Rusen; Zhou, Renwu; Wang, Shuai; Lan, Zhou; Zhang, Xianhui; Yin, Yingwu; Tu, Song; Yang, Size; Ye, Liyi
Graphical abstract: Highlights: Liquid-phase microplasma technology was used to assist in biomass liquefaction. The liquefaction rate of BSS reached 96% within 3 min. Plasma-assisted liquefaction makes extra heating needless. Plasma-assisted liquefaction can lessen the catalyst dosage. Plasma-assisted technology shows enormous potential for biomass fast liquefaction. Abstract: In this study, liquid-phase microplasma technology (LPMPT) was employed to facilitate the liquefaction of bamboo shoot shell (BSS) in polyethylene glycol 400 (PEG 400) and ethylene glycol (EG) mixture. Effects of liquefaction conditions such as liquefaction time, catalyst percentage, solvent/BSS mass ratio, PEG/EG volume ratio on liquefaction were investigated experimentally. The results showed that the introduction of LPMPT significantly shortened the liquefaction time to 3 min without extra heating. The liquefaction yield reached 96.73% under the optimal conditions. The formation of massive reactive species and instantaneous heat accumulation both contributed to the rapid liquefaction of BSS. Thus, LPMPT could be considered as a simple and efficient method for the assistance of biomass fast liquefaction.